The main directions of national metallurgy development in the context of global trends - N. I. Anelkin; A. V. Mantsevich; D. G. Voitekhovsky; S. A. Mozgov (Литьë и металлургия, 2023)
We are witnessing how today the world is facing new challenges and new revolutionary trends in terms of further technological development and the formation of a new sixth technological order that challenges established and commercially available technologies. The increasing complexity, breadth, depth and speed of change, volatile markets and breakthrough technologies require new thinking, readiness for change, and time forces us to move faster.The article contains an overview of global trends in industrial development, advanced technological trends and technologies for the development of domestic metallurgy, carried out in the period 2019–2022, based on the following materials: Internet resources of the world’s leading manufacturers and suppliers of technology and equipment in metallurgy; the Strategy “science and technology: 2018–2040”; the Concept of the National Strategy for Sustainable Development of the Republic of Belarus on the period up to 2035; the National Strategy for Sustainable Socio‑Economic Development of the Republic of Belarus for the period up to 2030; Programs of socio‑economic development of the Republic of Belarus for the period 2021–2025; Priority areas of scientific, scientific, technical and innovative activities for 2021–2025; the Eurasian Economic Union; the International Conference “Designing the Future. Problems of digital reality”; Significant events in the Republic of Belarus in 2021–2022 on the development of industry.